Anomalous flashovers of silicone rubber insulators under the artificial rain test - Krystian Leonard Chrzan; Henryk Marek Brzeziński (Archives of Electrical Engineering, 2021)
The wet flashover voltage of medium voltage insulators made of a silicone rubber is 8% lower than the wet flashover voltage of a porcelain insulator with an identical profile. These surprising results, obtained in 2012, were confirmed again in 2019. The flashover development on the composite insulator is very short (less than 30 ms). On the other hand, on the porcelain insulator, the flashover develops longer (1–3 seconds). The Koppelmann equation was modified, and the Obenaus model to calculate the flashover voltage of insulators under the artificial rain was presented. Attention was paid to the importance of insulator diameters and the phenomenon of water cascades.